2008
DOI: 10.1038/jp.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of death or bronchopulmonary dysplasia in preterm infants with respiratory failure

Abstract: Objectives: To identify the variables that predict death/physiologic bronchopulmonary dysplasia (BPD) in preterm infants with severe respiratory failure.Study Design: The study was a secondary analysis of data from the NICHD Neonatal Research Network trial of inhaled nitric oxide (iNO) in preterm infants. Stepwise logistic regression models and Classification and Regression Tree (CART) models were developed for the outcome of death or physiologic BPD (O 2 at 36 weeks post-menstrual age).Result: Death and/or BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 23 publications
1
85
0
2
Order By: Relevance
“…We also showed that lower weight was associated with earlier death, a finding supported by earlier studies. [29][30][31] Although several articles 32,33 report a higher readmission rate in the first year of life for patients with BPD in general, we could not report the readmission rate for the first year of life because the length of the initial hospital stay was very long. This length of stay is probably secondary to the need for extensive caregiver training in ventilator and tracheostomy care, as previously described.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…We also showed that lower weight was associated with earlier death, a finding supported by earlier studies. [29][30][31] Although several articles 32,33 report a higher readmission rate in the first year of life for patients with BPD in general, we could not report the readmission rate for the first year of life because the length of the initial hospital stay was very long. This length of stay is probably secondary to the need for extensive caregiver training in ventilator and tracheostomy care, as previously described.…”
Section: Discussionmentioning
confidence: 46%
“…Within the group of patients who were alive at the end of this study, 69 (83.1%) patients were weaned off the PPV and 60 (72.2%) patients were decannulated. Sixty-seven (97.1%) of 69 patients liberated from PPV were ARTICLE weaned within the first 5 years of life, with a median age at liberation of 24 months (IQR, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Similarly, 58 (96.7%) of the 60 decannulated patients completed this process within the first 6 years of life, with a median age at decannulation of 37.5 months (IQR, 31.5-45).…”
Section: Resultsmentioning
confidence: 99%
“…Incidência e principais fatores associados à falha de extubação em recém-nascidos com peso de nascimento < 1.250 gramas do desenvolvimento neuropsicomotor e óbito [1][2][3][4] . Esforços para limitar a duração da ventilação invasiva têm como objetivo principal reduzir essas complicações.…”
Section: Incidence and Main Risk Factors Associatedunclassified
“…Factors linked to BPD include: 1) low gestational age at birth (Kraybill et al, 1989;Darlow & Horwood, 1992;Antonucci et al, 2004;Ambalavanan & Novak, 2003), 2) low birth weight (Darlow & Horwood, 1992;Hakulinenet al, 1988;Avery et al, 1987;Ambalavanan et al, 2008), 3) growth restriction (small for gestational age) (Durrmeyer X et al, 2011;Lal Mk et al, 2003;Zeitlin J et al, 2010), 4) male sex (Kraybill et al, 1989;Darlow & Horwood, 1992;Ambalavanan & Novak, 2003;Avery et al, 1987), and 5) white race (Avery et al, 1987;Palta et al, 1991). In a recent cohort, BPD affected 85% of infants born at 22 weeks' gestation vs. 23% of those born at 28 weeks' (Stoll et al, 2010).…”
Section: Demographic Factorsmentioning
confidence: 99%